Primary malignant rhabdoid tumor of the central nervous system - a comprehensive review - (:unkn) unknown (SPRINGER, 2005)
This paper presents the case of an eight-year-old girl who presented with headache and vomiting and was found to harbor a right fronto-temporo-parietal, partially cystic and centrally solid tumor that measured 11 x 8 x 7 cm. This vascular tumor was gross totally removed. The initial histopathologic diagnosis was hemangiopericytoma and the patient received a total dose of 5330 cGy of external cranial radiation. Twelve months later, the patient presented with left lower quadrant pain and limping and the spinal MR scans showed metastases at T4-5, T7, T12-L1 and L3 levels. The voluminous lesion at T12-L1 was surgically removed. Histopathological examination of both specimens revealed that both tumors in fact were malignant rhabdoid tumor (MRT). The patient did not benefit from spinal surgery and died 4 months later. A review of the literature has shown that since Briner et al'. first report in 1985 [Pediatr Pathol 3: 117-118, 1985], 100 MRT cases have been published. More than two-thirds of reviewed cases presented with local recurrence or subarachnoid spread after a mean period of 6.9 months after diagnosis and died two months later. Infratentorial and pineal location and surgery limited to biopsy were poor prognostic indicators. Twenty-two cases remained alive at a mean period of 24.5 months. The longest survival with an intracranial MRT was 65 months. Of those remaining alive, 15 had no evidence of disease (NED). Our case is the first MRT case immunopositive for HMB-45 and has also shown that the MRT cells grow aggressive over time as demonstrated by a four-fold increase in MIB-1 labeling index.
Keywords: metastasis; prognosis; radiotherapy; rhabdoid tumor; ATYPICAL TERATOID/RHABDOID TUMOR; PRIMITIVE NEUROECTODERMAL TUMORS; NATIONAL-WILMS-TUMOR; STUDY-PATHOLOGY-CENTER; OF-THE-LITERATURE; TERATOID TUMOR; SUPPRESSOR GENE; MR FINDINGS; BRAIN; INFANCY